Immune Responses of Chickens Infected with Wild Bird-Origin H5N6 Avian Influenza Virus - Gao, Shimin; Kang, Yinfeng; Yuan, Runyu; Ma, Haili; Xiang, Bin; Wang, Zhaoxiong; Dai, Xu; Wang, Fumin; Xiao, Jiajie; Liao, Ming; Ren, Tao (Frontiers in Microbiology, 2017)
Since April 2014, new infections of H5N6 avian influenza virus (AIV) in humans and domestic poultry have caused considerable economic losses in the poultry industry and posed an enormous threat to human health worldwide. In previous research using gene sequence and phylogenetic analysis, we reported that H5N6 AIV isolated in February 2015 (ZH283) in Pallas’s sandgrouse was highly similar to that isolated in a human in December 2015 (A/Guangdong/ZQ874/2015), whereas a virus (i.e., SW8) isolated in oriental magpie-robin in 2014 was highly similar to that of A/chicken/Dongguan/2690/2013 (H5N6). However, the pathogenicity, transmissibility, and host immune-related response of chickens infected by those wild bird-origin H5N6 AIVs remain unknown. In response, we examined the viral distribution and mRNA expression profiles of immune-related genes in chickens infected with both viruses. Results showed that the H5N6 AIVs were highly pathogenic to chickens and caused not only systemic infection in multiple tissues, but also 100% mortality within 3–5 d post-infection. Additionally, ZH283 efficiently replicated in all tested tissues and transmitted among chickens more rapidly than SW8. Moreover, quantitative real-time polymerase chain reaction analysis showed that following infection with H5N6, AIVs immune-related genes remained active in a tissue-dependent manner, as well as that ZH283 induced mRNA expression profiles such as TLR3, TLR7, IL-6, TNF-α, IL-1β, IL-10, IL-8, and MHC-II to a greater extent than SW8 in the tested tissues of infected chickens. Altogether, our findings help to illuminate the pathogenesis and immunologic mechanisms of H5N6 AIVs in chickens.